(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
Citizenship and Ius Scholae: A Constitutional Issue The article delves into the reform proposals on Italian citizenship, which have once again become the focus of political debate, to enable a comprehensive legal pathway towards the full integration of individuals of foreign origin into the Italian political community. The paper analyzes certain aspects of legislative interventions discussed and approved in the past decade, particularly in relation to the ius scholae, which refers to the acquisition of citizenship after the completion of a cycle of studies or equivalent educational pathways. The objective is to highlight the substantial benefits that would strengthen the institution of citizenship within the Italian legal system should the definitive incorporation of educational and schooling requirements for foreigners be included in the Italian nationality law.